Himantura randalli sp. nov., a new whipray (Myliobatoidea: Dasyatidae) from the Persian Gulf - Last, Peter R.; Manjaji-Matsumoto, B. Mabel; Moore, Alec B. M. (Zootaxa, 2012)
A new whipray, Himantura randalli sp. nov., described from material collected off Bahrain, Kuwait and Qatar, appearsto be endemic to the Persian Gulf. It has been frequently confused with forms of the more widely distributed whiprayHimantura gerrardi Gray and other presently unidentified species from the Indian Ocean. Himantura randalli sp. nov. isdistinguished from these species by a combination of characters, i.e. disc shape, morphometrics, squamation (includingits rapid denticle development and denticle band shape), plain dorsal disc coloration, and whitish saddles on a dark tail inyoung. It is a medium-sized whipray with a maximum confirmed size of 620 mm disc width (DW) and a birth size ofaround 150–170 mm DW. Males mature at approximately 400 mm DW. Himantura randalli sp. nov. is relatively abundantin the shallow, soft-sedimentary habitats of the Persian Gulf from where it is commonly taken as low-value or discarded bycatch of gillnet and trawl fisheries.